Eco-Friendly Adsorbent from Waste of Mint: Application for the Removal of Hexavalent Chromium - Fatima Khammour; Fatouma Mohamed Abdoul-Latif; Ayoub Ainane; Jalludin Mohamed; Tarik Ainane (Journal of Chemistry)
A serious environmental disaster is looming on the horizon due to the indiscriminate release of heavy metals into the soil and wastewater from human industrial practices. In this study, waste mint (WM) was used to remove chromium(VI) from aqueous solution using batch experiments. The adsorbent material (WM) was characterized using scanning electron microscopy coupled with energy dispersive analysis of X-ray spectroscopy (SEM-EDS), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and thermal gravimetric analysis (TGA). The adsorption parameters optimized were as follows: pH solution (2–11), initial concentration of Cr(VI) (10–50 mg/L), adsorbent dose (0.1–10 g/L), and temperature conditions (298 K, 308 K, and 318 K). The experimental data fitted well to the fractional power kinetic model (0.97≤R2≤ 0.99) and Langmuir isotherm (R2 = 0.984) with a maximum adsorption capacity Qmax = 172.41 mg/g. The thermodynamic parameters for Cr(VI) sorption were also calculated, confirming that the adsorption process was spontaneous and accompanied by an exothermic adsorption (−4.83 ≤ ΔG ≤ −3.22 kJ/mol and ΔH = −28.93 kJ/mol). The Cr(VI) removal percentage was within the range of 41–98%, and the highest removal was noted at pH = 2. The results of the present study suggest that WM is a potential low-cost adsorbent for the removal of chromium(VI) from aqueous solutions.